PENGGUNAAN KATALOG DI PERPUSTAKAAN SMA MUHAMMADIYAH 1 PALEMBANG - Dwi Putri, Ramelia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This article discusses in full about cataloging at SMA Muhammadiyah 1 Palembang, Catalog is basically a list if it is associated with a library, a library catalog contains a list of book collections that have been arranged systematically. In relation to the library, a library catalog is a list of library materials both in the form of books and non-books such as magazines, newspapers, microfilms, slides and others stored in a library or a group of libraries. This research discusses starting from the book collection, catalog system, and catalog usage. Using qualitative research methods with direct interviews to the head of the library, the purpose of this research is to find out whether the SMA Muhammadiyah 1 Palembang library has been effective in using the catalog system carried out. The result of this research is knowing that SMA Muhammadiyah 1 Palembang still uses a manual catalog system and has not switched to digital, the use of card catalogs is not used by students in searching library materials.